Antioxidant Evaluation of Coriander Extract and Ascorbyl Palmitate in Sunflower Oil Under Thermoxidation - Angelo, Priscila M. [UNESP]; Jorge, Neuza [UNESP] (Springer, 2008)
The objectives of this study were to evaluate isolated and synergistic antioxidant effects of coriander extract and ascorbyl palmitate (AP) in sunflower oil subjected to thermoxidation, and to verify their influence on the oxidative resistance of alpha-tocopherol, which occurs naturally in safflower oil. Sunflower oil samples with 1,600 mg/kg coriander extract, 500 mg/kg AP, and a mixture of those two antioxidants were heated to 180 degrees C for 30 h. Samples were taken at 0, 10, 20 and 30 h and analyzed to evaluate oxidative stability, total polar compounds, and alpha-tocopherol content. Results were subjected to variance analyses and Tukey tests at a 5% significance level, in a factorial scheme, to an entirely casual delineation. Coriander extract and AP delayed lipid oxidation and promoted the retention of alpha-tocopherol when added separately to sunflower oil and subjected to thermoxidation. The mixture of the antioxidants showed a higher antioxidant effect, thereby demonstrating their synergy under these conditions.
Keywords: Coriander extract; Ascorbyl palmitate; Oxidative stability; Polar compounds; alpha-Tocopherol; Thermoxidation